PEDOT:PSS nano-particles in aqueous media: A comparative experimental and molecular dynamics study of particle size, morphology and z-potential - Jain, Karishma; Mehandzhiyski, Aleksandar Y.; Zozoulenko, Igor; Wågberg, Lars (Journal of colloid and interface science, 2021)
[Display omitted] PEDOT:PSS is the most widely used conducting polymer in organic and printed electronics. PEDOT:PSS films have been extensively studied to understand the morphology, ionic and electronic conductivity of the polymer. However, the polymer dispersion, which is used to cast or spin coat the films, is not well characterized and not well understood theoretically. Here, we study in detail the particle morphology, size, charge density and zeta potential (z-potential) by coarse-grained MD simulations and dynamic light scattering (DLS) measurements, for different pH levels and ionic strengths. The PEDOT:PSS particles were found to be 12 nm–19 nm in diameter and had a z-potential of −30 mV to −50 mV when pH was changed from 1.7 to 9, at an added NaCl concentration of 1 mM, as measured by DLS. These values changed significantly with changing pH and ionic strength of the solution. The charge density of PEDOT:PSS particles was also found to be dependent on pH and ionic strength. Besides, the distribution of different ions (PSS−, PEDOT+, Na+, Cl−) present in the solution is simulated to understand the particle morphology and molecular origin of z-potential in PEDOT:PSS dispersion. The trend in change of particle size, charge density and z- potential with changing pH and ionic strength are in good agreement between the simulations and experiments. Our results show that the molecular model developed in this work represents very well the PEDOT:PSS nano-particles in aqueous dispersion. With this study, we hope to provide new insight and an in-depth understanding of the morphology and z-potential evolution in PEDOT:PSS dispersion.